Upaya Meningkatkan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Discovery Learning pada Peserta Didik Kelas IX.6 SMP Negeri 42 Palembang - Sri Oktaviana (Departement of Mathematics Education, 2022)
The application of ordinary learning carried out in class IX.6 at SMP Negeri 42 Palembang has not used an effective learning model, the average value of student learning outcomes is 66 and learning completeness reaches 36.67% or there are 11 students out of 30 students who have finished studying. This is because students still feel they are not optimal and do not understand what the teacher is explaining so that learning outcomes are still low. class IX.6 SMP Negeri 42 Palembang with the number of students 30 people. This study aims to determine the increase in student learning outcomes in class IX.6 SMP Negeri 42 Palembang after the implementation of the Discovery Learning learning model so that learning Mathematics becomes more fun and raises the creativity of participants educate. This research was formulated, namely